Perancangan Strategi Digital Marketing Pada Brand Sofia And Jenna Menggunakan Metode SOSTAC - Saffanah, Vina Putri; Wulandari, Sari; Rohayati, Yati (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The development of the Muslim Fashion Industry is increasingly rapid every year. This indicates that competition is getting tighter and the potential market for Muslim fashion in Indonesia continues to increase. Sofia and Jenna are one of the business actors operating in the Muslim fashion sector. Sofia and Jenna is a local brand that produces its own clothes (self-manufactured) which was founded in 2020. Even though it has been operating for several years, sales of Sofia and Jenna from January 2023 to October 2023 experienced fluctuations, in fact sales growth was still below Indonesian fashion industry. This is caused by several factors, namely low heart share and suboptimal use of digital marketing platforms, so this affects Sofia and Jenna's sales performance. For this reason, deeper observations were made regarding alternative solutions related to product, place, resource and promotion aspects. Of these four aspects, there is one aspect that shows the roots of the problem more than the other aspects, namely the promotion aspect. This research was conducted using the SOSTAC method which went through six stages, namely Situation Analysis, Objectives, Strategy, Tactics, Action, and Control. The aim of designing this digital marketing strategy is as a promotional medium and is expected to increase sales and marketing performance so that it can increase awareness of the Sofia and Jenna brand. Based on the digital marketing strategy design, this final project produced a design for the use of Social Media Optimization (SMO), Content Marketing, Partnership, Video Marketing, Linktree, User Generated Content (UGC), and Mobile Commerce Optimization tools. Then, the design is visualized using a Strategy Map. Through a structured and data-based approach, Sofia and Jenna are expected to be able to improve their position in the Muslim fashion market, as well as increase competitiveness and consumer loyalty towards the brand.